Need Based Information Media for Farmers in Hill Regions of Uttarakhand: Implications for Extension (Indian Journal of Extension Education, 2021)
Farmers use different information sources and channels for seeking reliable, timely and relevant information on improved agricultural practices. Developing appropriate farmer educational and marketing strategies will depend on how farmer groups differ in their information search behavior. Understanding what information farmers need, how they search for their information, which sources they depend on for accessing information can help in designing effective extension programs. The study examined farmer’s communication characteristics with an intent to assess farmer’s accessibility and use of extension media and information sources for fulfilling their information needs pertaining to agricultural and allied activities in three hill districts of Uttarakhand state. A sample of 1318 farmers was selected through a stratified random sampling technique. Interpersonal communication sources were used more by farmers as these were more easily available and accessible to obtain information related to agriculture. Majority of farmers were categorised as low searchers. Gender, primary occupation, land size and education significantly affected search behaviour of farmers. Implications for policy and extension have been given for improving information dissemination among farmers of hill regions. Emphasis on extension system providing a context for the flow of authentic knowledge through authentic media among farming communities on an equal basis is emphasized.